Simulation studies of superconducting afterburner operation for the European XFEL. Issue 1 (1st December 2022) - Lechner, C; Casalbuoni, S; Geloni, G; Marchetti, B; Serkez, S; Sinn, H
Abstract: European XFEL is a multi-beamline x-ray free-electron laser (FEL) user facility driven by a superconducting accelerator with a nominal photon energy range from 250 eV to 25 keV. An afterburner undulator based on superconducting undulator technology is currently being investigated to enable extension of the photon energy range towards harder x-rays. This afterburner undulator would be installed downstream of the already operating SASE2 FEL beamline, emitting at the fundamental or at a harmonic of the upstream undulator system. In this contribution we describe the layout under study and present numerical simulations.